2014
DOI: 10.1186/1471-2229-14-87
|View full text |Cite
|
Sign up to set email alerts
|

The onset of grapevine berry ripening is characterized by ROS accumulation and lipoxygenase-mediated membrane peroxidation in the skin

Abstract: BackgroundThe ripening of fleshy fruits is a complex developmental program characterized by extensive transcriptomic and metabolic remodeling in the pericarp tissues (pulp and skin) making unripe green fruits soft, tasteful and colored. The onset of ripening is regulated by a plethora of endogenous signals tuned to external stimuli. In grapevine and tomato, which are classified as non-climacteric and climacteric species respectively, the accumulation of hydrogen peroxide (H2O2) and extensive modulation of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 77 publications
4
88
0
2
Order By: Relevance
“…The ubiquity of membrane substrate for lipoxygenases can explain the persistence of singlet oxygen production detected here even after cell death. Developmentally programmed singlet oxygen production that correlated with SOSG fluorescence was traced to lipoxygenase activity in grapevine berry skin ripening (Pilati et al, 2014). Indeed, in the case of ripening grape berry, over 10% of the side chains were oxidized to membrane bound 13-peroxy galactolipids.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of membrane substrate for lipoxygenases can explain the persistence of singlet oxygen production detected here even after cell death. Developmentally programmed singlet oxygen production that correlated with SOSG fluorescence was traced to lipoxygenase activity in grapevine berry skin ripening (Pilati et al, 2014). Indeed, in the case of ripening grape berry, over 10% of the side chains were oxidized to membrane bound 13-peroxy galactolipids.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 levels increase in the berry skin of grape (Vitis vinifera 'Pinot Noir') at the onset of ripening (veraison), when the most crucial events during berry ripening occur, including the change in color of the skin (Pilati et al, 2014). Studies on tomatoes also have revealed an elevation in H 2 O 2 levels during changes in color of the skin (Jimenez et al, 2002;Kumar et al, 2016).…”
Section: Photooxidative Stress In Leaves Flowers and Fruitsmentioning
confidence: 99%
“…Porém, interações diretas entre estas vias ainda carecem de evidências, impossibilitando ainda uma melhor compreensão da atuação dos hormônios durante o desenvolvimento das bagas (Fortes et al, 2015). Outros mecanismos de controle de desenvolvimento também podem estar envolvidos como sinalizadores do amadurecimento, como o acúmulo de algumas espécies reativas de oxigênio (ROS) em concentrações e compartimentos celulares específicos (Pilati et al, 2014 …”
Section: (Anthocyanins) E Bobeica Et Al (2015) (Sugars Acidity Andunclassified